2021
DOI: 10.1177/1742271x211047945
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care contrast enhanced lung ultrasound and COVID-19

Abstract: Objectives Bedside lung ultrasound has been indispensable during the coronavirus disease 2019 (COVID-19) pandemic, allowing us to rapidly assess critically unwell patients. We demonstrate the unique application of contrast-enhanced ultrasound with the aim of further understanding this disease. Methods Patient demographics were recorded alongside recent cross-sectional imaging and inflammatory markers. Ultrasound was conducted by experienced operators in a portable setting. Conventional six-point lung ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…53 Notably, avascular areas suggestive of pulmonary infarctions were detected on LUS in 100% of patients enrolled in the study, despite 79% having a recent negative CT pulmonary angiogram. 53…”
Section: The Special Case Of Coronavirus Disease 2019mentioning
confidence: 88%
See 2 more Smart Citations
“…53 Notably, avascular areas suggestive of pulmonary infarctions were detected on LUS in 100% of patients enrolled in the study, despite 79% having a recent negative CT pulmonary angiogram. 53…”
Section: The Special Case Of Coronavirus Disease 2019mentioning
confidence: 88%
“…The authors demonstrated that the degree of infarction correlates with the severity of COVID-19 pneumonia (r ¼ 0.4) on CT scan and with inflammatory markers, and that these areas improved as patients recovered. 53 Notably, avascular areas suggestive of pulmonary infarctions were detected on LUS in 100% of patients enrolled in the study, despite 79% having a recent negative CT pulmonary angiogram. 53 Lung Ultrasound versus Computed Tomographic Pulmonary Angiography CTPA is the gold standard for the diagnosis of PE, thanks to its high sensitivity and specificity.…”
Section: Role Of Contrast-enhanced Ultrasoundmentioning
confidence: 88%
See 1 more Smart Citation
“…20 Studies that used contrast-enhanced ultrasound in patients with pneumonia found perfusion defects within consolidations, suggesting that it could be caused by ischemic or necrotic changes that differ from inflammatory causes in consolidations. 21,22 This indicates that the use of contrast-enhanced LUS could provide pathogenetic interpretations of consolidations in patients with pneumonia. Future studies aiming to quantify the types and stages of pneumonia using advanced ultrasound imaging techniques are encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…The LUS features of consolidation in patients with pneumonia include a hypoechoic area with irregular and serrated margins that exhibits heterogeneous echotexture caused by focal air inclusions, and homogeneous sub-pleural section 20 . Studies that used contrast-enhanced ultrasound in patients with pneumonia found perfusion defects within consolidations, suggesting that it could be caused by ischemic or necrotic changes that differ from inflammatory causes in consolidations 21,22 . This indicates that the use of contrast-enhanced LUS could provide pathogenetic interpretations of consolidations in patients with pneumonia.…”
Section: Discussionmentioning
confidence: 99%